Somatic Experiencing® Informed Therapeutic Group for the Care and Treatment of Biopsychosocial Effects upon a Gender Diverse Identity - Briggs, Paul C.; Hayes, Sage; Changaris, Michael (Frontiers in Psychiatry, 2018)
Background Somatic Experiencing® (SE™) is a resiliency-based treatment for autonomic nervous systems dysregulation syndromes, such as posttraumatic stress disorder, anxiety, depression, and physical syndromes like chronic pain, migraines, and fibromyalgia. “Transgender/gender non-conforming/gender variant” describes people whose gender identity/expression is different, at least part of the time, from the sex assigned at birth. Research indicates transgender individuals have a higher incidence of depression, anxiety, victimization, and discrimination. SE™ tools may support transgender/gender non-conforming individuals to increase resilience in the face of discrimination and social injustice. Methods This study is a pretest posttest within group (N = 7) pilot study assessing the impact of a 10 session SE™ based group treatment on depression (PHQ-9), anxiety (GAD-7), somatic symptoms (PHQ-15), quality of life (QoL) (WHOQoL-BREF), and coping with discrimination (CDS) for a cohort of seven individuals identifying as transgender/gender non-conforming. Materials were created in collaboration with members of the LGBTQIA community. Care was taken to be inclusive of gender non-conforming identities and culturally responsive in design. Results Participants described their gender identities as: non-binary, female to male, male to female, and gender fluid. Participants had significant increase in psychological QoL (psychological well-being) (WHOQoL-BREF) p = 0.004, SD = 2.31, with a modest effect size of d = 0.71. Some likely impacts of historical effect discussed. No other clinical or QoL outcomes were statistically significant. However, one outlier was identified in the dataset. When this outlier was excluded there was a trend toward significant reduction in depression symptoms (PhQ-9) p = 0.097, SD = 3.31 and a modest effect size of d = 0.68; somatic symptoms (PhQ-15) p = 0.093, SD = 3.52 and a modest effect size of d = 0.72. Conclusion These data indicate that a brief 10 session intervention of SE™ could have a meaningful impact on symptoms of depression, somatization, and QoL for gender non-conforming individuals. Further research is warranted. Limitations First, this study has a small sample size limiting statistical power and generalizability. Second is a history effect. Less than 1 week prior to final data collection, there was a significant hate-motivated act in Florida targeting the LGBTQIA community.